2021
DOI: 10.3389/fpsyg.2021.619340
|View full text |Cite
|
Sign up to set email alerts
|

Is Creative Description Always Effective in Purchase Intention? The Construal Level Theory as a Moderating Effect

Abstract: Recent years has witnessed a rapid growth in online shopping. This paper draws from the construal level theory to examine the divergent effects of the creative text descriptions of products on consumers' purchase intention in an online context. It also investigates consumers' construal level and the moderating role of construal level in this relationship. An assumption has been made that the creative description embraces more rhetorical devices with analogies. In doing so, such texts are in need of consumers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
(173 reference statements)
0
8
0
Order By: Relevance
“…Companies can use machine learning to quickly and effectively identify consumers with different construal levels based on their online behavior data [ 87 ]. Companies can also collect information from consumers and build consumer profiles to help identify consumers with different construal levels [ 60 , 88 ]. Alternatively, some elements can be used to induce consumers to form a specific construal level, such as using language or imagery that indicates the present or the future [ 63 ] or manipulating the visual height of advertising images [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Companies can use machine learning to quickly and effectively identify consumers with different construal levels based on their online behavior data [ 87 ]. Companies can also collect information from consumers and build consumer profiles to help identify consumers with different construal levels [ 60 , 88 ]. Alternatively, some elements can be used to induce consumers to form a specific construal level, such as using language or imagery that indicates the present or the future [ 63 ] or manipulating the visual height of advertising images [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scholars in the field of consumer behavior gradually realized the importance of the construal-level theory for understanding consumer behavior (Li et al ., 2009; Kim and John, 2008). They used the theory of construal level to study the persuasion effects of product appeal (Hernandez et al ., 2015), advertisement type (Sun and Miao, 2018), advertisement text descriptions (Yao et al ., 2021) and so on. The comparison between the current research and previous researches is shown in Table 2.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals with low construal levels usually use a specific information processing style, look closely at things, and initiate concrete mental representations. In contrast, people with high levels of understanding tend to present relatively abstract mental representations [37,38]. Fluency is an individual's subjective experience of how easy it is to process information, and visual fluency is mainly affected by the objective characteristics of information and individual traits [39].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, construal level user traits are an important factor that affects the visual cognition of information concreteness. In past research, relevant scholars have carried out extensive discussions and tests on the matching degree of user construal level traits and information concreteness in various fields [38,47], but as far as we know, in the interface environment, how the user's construal level traits interact with the concreteness of the combined icon, and thus how they affect the user's decision-making process, still needs to be verified. So, we pursued this question.…”
Section: Introductionmentioning
confidence: 99%